Social Entrepreneurship and Sustainable Business Models The Case of India (Springer International Publishing, 2018)
"India is one of the most important and also most interesting places for social entrepreneurship. This books bring together the leading scholars in this area and paints a vivid picture of what has already been achieved and where future challenges lie. Highly recommended!" Kai Hockerts, Professor of Social Entrepreneurship, Copenhagen Business School, Denmark "This edited volume is one of its kind. By unravelling the meaning of social entrepreneurship, impact measurement, impact investing and sustainable incubators, it promotes scholarship on social entrepreneurship in India, by drawing on a context-sensitive, indigenous perspective" Jacques Defourny, Director, Centre for Social Economy HEC Liège Management School, University of Liège, Belgium Addressing the need for further theorisation and operationalisation of social entrepreneurship in India, this edited collection provides a critical and deeper understanding of the social entrepreneurial ecosystem. Covering topics such as entrepreneurial intentions, empathy, impact investment and standardised social measures, the contributors explore the potential of social entrepreneurship and sustainable business models in Indian context. Offering empirical cases and presenting a realistic perspective of the social entrepreneurship landscape in India, this collection will undoubtedly be of value to those interested in creating a social and sustainable impact in business and society.